1994
DOI: 10.1177/096032719401300205
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Cisplatin Toxicity in Rat Renal Cortical Slices by Dithiothreitol In vitro

Abstract: 1 The protective effects of dithiothreitol (DTT) on cisplatin-induced nephrotoxicity were investigated with rat renal cortical slices. 2 The nephrotoxic effects of cisplatin (2 mmol l-1) were manifested in several ways: the Na+ and water content were increased while K+ was decreased. The malondiadehyde (MDA) concentration in the slices and the lactate dehydrogenase (LDH) released into the medium were increased. The uptake of p-aminohippurate (PAH), the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Our observation is in contrast with reports showing that apoptosis is associated with a decrease in ⌬⌿ m caused by unrestrained opening of the mitochondrial permeability transition pore (MPTP), which results in the release of proapoptotic proteins from the mitochondrial intermembrane space to the cytoplasm and activation of caspases (42)(43)(44). It has also been suggested that cisplatin causes a decline in ⌬⌿ m and opening of MPTP in RPTC as assessed by rhodamine 123 uptake (33,45). However, these studies used a high concentration of cisplatin (2 mM) that causes oncosis and mitochondrial depolarization rather than apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation is in contrast with reports showing that apoptosis is associated with a decrease in ⌬⌿ m caused by unrestrained opening of the mitochondrial permeability transition pore (MPTP), which results in the release of proapoptotic proteins from the mitochondrial intermembrane space to the cytoplasm and activation of caspases (42)(43)(44). It has also been suggested that cisplatin causes a decline in ⌬⌿ m and opening of MPTP in RPTC as assessed by rhodamine 123 uptake (33,45). However, these studies used a high concentration of cisplatin (2 mM) that causes oncosis and mitochondrial depolarization rather than apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these kinases results in p53 phosphorylation, activation of caspase-3, generation of catalytic domains of different isozymes of protein kinase C (PKC), including PKC-␦, PKC-⑀, and PKC-, and is followed by cell death (30 -32). PKC isozymes have been implicated in cisplatin toxicity in renal proximal tubules as well (4,33). It has been shown that cisplatin administration in vivo increases protein levels of PKC-␣ in renal proximal tubules and that pretreatment with general protein kinase inhibitors protects kidneys from cisplatin-induced injury (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mechanism of CDDP-induced ROS production remains unclear, mounting evidence has indicated that antioxidant enzymes or sulfhydryl compounds are able to reduce the toxicity of CDDP. 11,43,44) We also have reported that combined expression of SOD and GSHPx by gene transfer caused resistance to CDDPin HeLa cells. 10) Therefore the utilization of MT null cells for developing CDDP-resistant cells may permit the detection of other important antioxidants associated with the acquisition of CDDP resistance.…”
Section: Discussionmentioning
confidence: 89%
“…Kinetic studies of Pt drug accumulation have revealed a slow cellular uptake process, mediated at least in part by transporters/carriers [4] that are influenced by temperature, pH [5][6][7], K þ ions [8] and reducing agents [9][10][11] much like the uptake of Cu [12]. Efflux of Pt drugs is active and biphasic, with a fast initial phase and a very slow secondary phase [13].…”
Section: Introductionmentioning
confidence: 99%